Carbon isotope discrimination in Quercus ilex resprouts after fire and tree-fell - Fleck, Isabel; Grau, Daniel; Sanjose, M.; Vidal, D. (Oecologia, 1996)
Ecophysiological differences related to photo- synthesis were compared in holm oak Quercus ilex leaves from undisturbed holm-oak vegetation, resprouts after fire and resprouts after tree-fell. No significant dif- ferences in any parameter measured were observed be- tween the two kinds of resprout throughout the first growing season following disturbance. Resprouting leaves showed lower carbon isotope discrimination (A) and intercellular CO 2 concentration (Pi), and higher pho- tosynthesis, leaf conductance and transpiration rates than leaves from undisturbed stands. Nitrogen, soluble protein content and ribulose bisphosphate carboxylase (RuBP- Case) activity were 88%, 96% and 45% higher respec- tively, in both kinds of resprout. The results indicate that photosynthetic capacity, rather than stomatal conduc- tance, is the limiting factor in photosynthesis in re- sprouts. Chlorophyll content and chlorophyll a/b ratio did not differ between resprouts and undisturbed leaves, indicating that the observed differences were not a result of differences in light environment during leaf develop- ment. Leaf mass per area (LMA), was 80% higher in the resprouts, and was negatively related (r= -0,86) to A and positively related (r=0.87) to N content. Enhanced car- bon assimilation after disturbances resulted in higher wa- ter use efficiency, as indicated by lower A values in the resprouts. We conclude that the cause of defoliation was not relevant in the physiology of the resprouts, suggest- ing the importance of underground organs.
Keywords: carbon isotope discrimination; Fire and tree-fell resprouts; Gas exchange; RuBPCase activity

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I.; Grau, D.; Sanjose, M.; Vidal, D. (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell